Operculum shape variation in Theodoxus Montfort, 1810 (Gastropoda: Neritidae) - Marković, Vanja; Vujić, Vukica; Ilić, Marija; Tomović, Jelena; Nikolić, Vera; Karan-Žnidaršič, Tamara (Zootaxa, 2019)
The operculum morphology of neritid snails of genus Theodoxus Montfort, 1810 yields important species-specific taxonomic characters. This study is the first attempt to describe morphological differences in snails based on operculum shapes using a geometric morphometric approach. We examined the variability of opercular shapes between sexes and among populations and species based on 91 opercula of adult specimens belonging to six populations of three species of Theodoxus from the central Balkan and the southern border of the Pannonian plain. There are no sex-related differences in operculum shape and size in the studied species. The presence of shape variations influenced by size (allometry) was confirmed for T. danubialis (C. Pfeiffer, 1828) indicating that allometry could be a component of the morphological variation of this species. At the intraspecific level, phenotypic plasticity of operculum shape was found in T. danubialis and T. fluviatilis (Linnaeus, 1758). Of particular interest is the lack of morphological variability in the rare and endangered T. transversalis (C. Pfeiffer, 1828). At the species level a clear morphological distinction of T. fluviatilis from T. danubialis and T. transversalis was detected, confirming that the operculum with a rib could be used as a species-specific morphological character. The main morphological differences between species are an outwardly-stretched opercular/apophysal rib and a shortened tip of the opercular plate in T. fluviatilis, compared to the same structures in T. danubialis and T. transversalis.